2022
DOI: 10.3389/fpsyg.2021.831972
|View full text |Cite
|
Sign up to set email alerts
|

Well-Being of Teachers: The Role of Efficacy of Teachers and Academic Optimism

Abstract: In previous decades, the well-being of teachers has been at the center of the attention of researchers in several practical investigations on various subjects such as language learning. The objective of this review is to clarify this construct and add new information on the predominance of the well-being of teachers and organize factors impacting it. Nevertheless, among factors influencing the levels of well-being, the focus of this review is on two constructs, namely, optimism “as a new concept in positive ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
(36 reference statements)
2
8
0
Order By: Relevance
“…Most studies found a negative association between student–teacher relationships (STR) and the risk factor of dropping out ( Lee and Burkam, 2003 ; Murray and Malmgren, 2005 ; Barile et al, 2011 ; Bergeron et al, 2011 ; Wang et al, 2013 ; Frostad et al, 2014 ; Littlecott et al, 2019 ; Song, 2021 ; Zheng, 2021 ). This means that in schools where there is a positive STR, there are low dropout rates.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…Most studies found a negative association between student–teacher relationships (STR) and the risk factor of dropping out ( Lee and Burkam, 2003 ; Murray and Malmgren, 2005 ; Barile et al, 2011 ; Bergeron et al, 2011 ; Wang et al, 2013 ; Frostad et al, 2014 ; Littlecott et al, 2019 ; Song, 2021 ; Zheng, 2021 ). This means that in schools where there is a positive STR, there are low dropout rates.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…Academic optimism concept has been investigated in relation to teacher professional learning [ 26 ], student achievement [ 49 , 50 ], work engagement [ 42 ] and distributed leadership [ 51 , 52 ]. This research evidence reveals first, that distributed leadership has a positive influence on academic optimism [ 51 , 52 ] and second, that academic optimism is related with students' learning achievement as well as teacher professional learning [ 26 , 50 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although there has been a lack of sufficient research on the effects of teacher leadership on teacher efficacy, the positive effects of transformational leadership on teacher efficacy imply that the effects of teacher leaders, who essentially function as transformational leaders in a school context, will also have positive effects (Leithwood et al, 1999). The positive effects of teacher efficacy on teacher well-being may be because teachers' positive beliefs about their capacity can enhance their optimism and in turn improve their well-being (Song, 2021). Meanwhile, strengthened efficacy beliefs will in turn build up strong teacher competence beliefs and a sense of independence.…”
Section: The Mediating Roles Of Teacher Efficacymentioning
confidence: 99%